Pengaruh Digital Marketing Terhadap Kinerja Penjualan Produk UMKM Durenstory Serang - Ayu Wandira; Fadilatun Nufus; Nur Kholisah; Riki Gana Suyatna; Silviah Silviah (Journal of Management and Social Sciences, 2024)
Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. The aim of this research is to increase knowledge and skills about digital marketing, especially social media, for Micro, Small and Medium Enterprises (MSMEs) business people to increase their sales and profits. Online marketing is suitable for new businesses or ventures. Of course it is cost effective, because you don't have to place products/services, can be controlled yourself without having to recruit employees, unlimited time or working hours, and has a wide market reach, because online marketing is supported by the presence of websites or social media (Facebook, Instagram, WA, etc.) and this research is also aimed at proving that there is an influence of digital marketing on the sales performance of Durenstory Serang MSME products. This research uses quantitative methods with a survey approach. Research data was obtained through a questionnaire distributed to 10 respondents who were Durenstory customers. Data were analyzed using simple linear regression analysis. The research results show that digital marketing has a positive and significant effect on the sales performance of Durenstory Serang MSME products. This means that the better the implementation of digital marketing, the higher the sales performance of Durenstory products. Based on the results of this research, it can be concluded that digital marketing is an effective strategy for improving the sales performance of MSME products. Therefore, MSMEs need to implement digital marketing strategies appropriately and sustainably.